Service-Oriented Perspectives in Design Science Research 6th International Conference, DESRIST 2011, Milwaukee, WI, USA, May 5-6, 2011. Proceedings - Jain, Hemant; Sinha, Atish P.; Vitharana, Padmal; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 6th International Conference on Service-Oriented Perspectives in Design Science Research, DERIST 2011, held in Milwaukee, WI, USA, in May 2011. The 29 revised full papers presented together with 5 revised short papers were carefully reviewed and selected from 50 submissions. The papers are organized in topical sections on design theory, design science research strategies, design methods and techniques, design evaluation, design guidelines, service-oriented perspectives in design science, process design, neuroscience in design research, and designing for social media.
Electronic reproduction.
Keywords: System design -- Congresses; System analysis -- Congresses; Electronic book